Hepatic fungal infection in a young beagle with unrecognised hereditary cobalamin deficiency (Imerslund‐Gräsbeck syndrome). (8th August 2014) - Kook, P. H.; Drögemüller, M.; Leeb, T.; Hinden, S.; Ruetten, M.; Howard, J.
<x xml:space="preserve">Abstract</x> A 12‐month‐old beagle presented for anorexia, pyrexia and vomiting. The dog had been treated intermittently with antibiotics and corticosteroids for inappetence and lethargy since five months of age. Previous laboratory abnormalities included macrocytosis and neutropenia. At presentation, the dog was lethargic, febrile and thin. Laboratory examination findings included anaemia, a left shift, thrombocytopenia, hypoglycaemia and hyperbilirubinaemia. Multiple, small, hypoechoic, round hepatic lesions were observed on abdominal ultrasound. Cytological examination of hepatic fine needle aspirates revealed a fungal infection and associated pyogranulomatous inflammation. The dog's general condition deteriorated despite supportive measures and treatment with fluconazole, and owners opted for euthanasia before hypocobalaminaemia was identified. Subsequent genomic analysis revealed a CUBN:c.786delC mutation in a homozygous state, confirming hereditary cobalamin malabsorption (Imerslund‐Gräsbeck syndrome). Similar to human infants, dogs with Imerslund‐Gräsbeck syndrome may rarely be presented for infectious diseases, distracting focus from the underlying primary disorder.